An NMR sample preparation case study: Considerations for the self-destructive protease caspase-6 - Nathanael J. Kuzio; Marco Tonelli; Jasna Fejzo; Jeanne A. Hardy (PLoS ONE, 2025)
Proteases represent a difficult family of proteins to purify, concentrate and store at homogeneity due to their toxicity during overexpression and their propensity to self-cleave, leading to the loss of sample stability and function. A protease of interest, caspase-6, is a member of the apoptotic family of caspases, and has been shown to be involved in human neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. Previous studies have elucidated key structural aspects and potential inhibition mechanisms of caspase-6 through various structural biology techniques such as x-ray crystallography and hydrogen-deuterium exchange mass spectrometry. However, caspase-6 undergoes a structural transition that requires atomic-resolution insight in solution to understand the conformational transitions and ensemble. This can be most optimally achieved using multi-dimensional biomolecular NMR. Prior attempts to study caspase-6 by NMR have failed due to challenges in sample preparation and insufficient protein concentration. Here, we document our exploratory strategy, which ultimately led to the refinement of crucial sample preparation steps and enabled us to obtain isotopically-labeled caspase-6 in yields suitable for heteronuclear NMR studies. We present this work in the hope that it will assist others in the preparation of difficult protein samples, particularly proteases.